Reactivity of Cetophenone and Its Derivatives with Semi-Empirise Methods Parameterizedmodel 6 (PM6) - Topan Setiawan; Saras Wati Banapon; Intan Sapsuha; Wahyu Yusup Duwila (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2022)
Cetophenone is used as an intermediate in the synthesis of flavones. In industry, Cetophenone is obtained as a by-product of the oxidation of ethyl benzene. The method used for modeling Cetophenone derivatives is a semi-empirical method using (PM6). The cetophenone derivative which has a larger energy difference is found in the compound 2-aceyiylisophyhaloitrile. The highest value of electronegativity and chemical hardness was found in the compound 2-aceyiylisophyhaloitrile and the greatest potential energy value was found in the compound 2-aceyiylisophyhaloitrile.